The Influence of Carrying out Investigative Audits on the Effectiveness of Disclosure of Corruption Crimes (Case Study of Representatives of the West Sumatra Province Financial and Development Supervisory Agency) - Ebit Bimas Saputra (Journal of Accounting and Finance Management, 2023)
The research aims to examine the effect of carrying out investigative audits on the effectiveness of disclosing criminal acts of corruption. This research was conducted at BPKP Representatives of West Sumatra Province. Data collection was carried out using a questionnaire as the primary data source. The data analysis method used is simple linear regression analysis. The results of the analysis show that the implementation of investigative audits has a positive and significant influence on the effectiveness of disclosing criminal acts of corruption. The ability of the independent variable to explain the dependent variable is 58.5%, while 41.5% is influenced by other variables outside this research.